Acute restraint stress alters sound-evoked neural responses in the rat auditory cortex. (2nd April 2015) - Ma, L.; Zhang, J.; Yang, P.; Wang, E.; Qin, L.
Highlights: Acute restraint stress temporally alters neural activities in the auditory cortex of rats. In most cases, stress enhances neural responses evoked by pure-tone and clicks. But in a minority of neurons, stress suppresses responses. Enhancement effect frequently occurred in the neurons with a low sensitivity to sound. Change of neural activity was associated with an elevation of corticosterone level. Abstract: Stress is known to elicit various adaptive or maladaptive responses in the nervous system function. Psychophysical studies have revealed that stress exposure induced the changes in auditory response that can be interpreted as a transient, stress-induced hypersensitivity to sounds. However, the underlying neural mechanism remains unresolved. Thus, in this study, we explored the neural activities of the auditory cortex (AC) in response to stress. We elicited stress by physically immobilizing rats and recorded the extracellular single-unit activities through the electrodes chronically implanted in the AC of rats. By comparing the spike activities of the same rat before, during and after immobilization, we found temporal and significant changes in the sound-evoked neural activities. In most cases, acute restraint stress enhanced neural responses evoked by pure-tones and click-trains, but in a minority of neurons, stress suppressed responses. The immobilization-induced enhancement was more frequently found in the neurons that originally had a low responsibility for sound stimuli. The enhancement effects on pure-tone response were reflected by an increase of response magnitude, decrease of response latency, and extension of bandwidth of tuning curve (BW). But the spontaneous firing rate and best frequency (BF) remained unchanged. Stress also increased the ability of neural response to synchronize to click-trains, even in the neurons whose response magnitude was not significantly increased. Taken together, these results provide direct evidence that stress alters the function of auditory system at the level of AC.